(untitled) (Third Sector Social Economic Review, 2025)
This study identifies the factors influencing dividend distribution policies. Dynamic Panel Data Analysis was applied using data from nine BIST-listed companies between 2013 and 2023. The data was obtained from the Refinitiv Eikon database, and analysis was performed using Eviews software. Descriptive statistics for the variables were presented, and Cross-Sectional Dependence, Panel Unit Root, Cointegration, and Panel Causality analyses were conducted. The stationarity relationship between the series was examined, and it was concluded that a causal relationship exists between the companies and the variables. The companies in the study were selected as those regularly distributing dividends over the past decade, and unlike similar studies, this research expanded the time frame (2013-2023), contributing to the literature. The results show a strong relationship between the dividend payout ratio and a company’s profitability and growth potential. An increase in earnings per share positively influences the dividend payout ratio, and companies with high market value tend to distribute a larger portion of profits to shareholders. Variables such as volume-based turnover and return on equity also influence dividend distribution policies. Effective dividend distribution policies significantly impact market value, and companies that implement successful policies can attract investor interest and increase their value.